Self-Assembled Bio-Nanomaterials: Synthesis, Characterization, and Applications - Wei, Gang (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Biomolecular self-assembly provides a green, facile, and highly effective method to synthesize various functional nanomaterials that have exhibited considerable potential in the fields of nanotechnology, materials science, biomedicine, tissue engineering, food science, energy storage, and environmental science. In this collection of articles, we presented recent advance in the synthesis, characterization, and applications of self-assembled bio-nanomaterials. In a comprehensive review article, the controlled self-assembly of biomolecules including DNA, protein, peptide, enzymes, virus, and biopolymers via internal interactions and external simulations is introduced and discussed in detail. In other research articles, the self-assembly of DNA, protein, peptide, bio-drugs, liquid crystal polycarbonates, and diblock copolymers to various biomimetic/bioinspired nanomaterials and their potential applications in nanopatterning, sensors/biosensors, drug delivery, anti-parasite, and water purification are demonstrated.
English
Keywords: graphene oxide; membrane; spindle-like nanoparticles; lamellar diblock copolymer; pattern transfer; flash nanoprecipitation; interactions; micromechanical biosensor; multiscale method; elastic property; cholesteryl; modular coassemble; Meloidogyne incognita; natural frequency; protein; nanoimprint lithography; external stimulations; ROS detection; DNA film; Abamectin; polymeric prodrug; amphipathic polycarbonates; biocompatibility; synergistic codelivery; amphiphilic block copolymers; nanostructures; self-assembly; stimulisensitive release; biomolecules; directed self-assembly; water purification; drug release; triphenylphosphonium; dicyanostilbene; polyhedral oligomeric silsesquioxane (POSS); liquid crystal